Experimental study on coal seam permeability enhancement and CO2 permeability caused by supercritical CO2 - Yu, Yongjiang; Liu, Jingjing; Yang, Yuntao; Wu, Di; Zhai, Wenbo; Miao, Feng (Frontiers in Earth Science, 2023)
Permeability is one of the most important parameters for characterizing fluid flow and production from reservoirs. In this paper, experimental studies on the percolation, permeability, and adsorption of supercritical CO2 in coal seams were carried out, taking into account the effects of injection pressure and temperature, comparing the changes in longitudinal wave velocity of specimens before and after the tests, and analyzing the permeability effect of supercritical CO2 on raw coal specimens. The test results showed that when the volume stress was 36 MPa, the permeability of supercritical CO2 in coal increased by 93%, on average, compared with that of CO2. The modified D-R model was used to fit the adsorption data, and it was found that the excess adsorption capacity of supercritical CO2 by coal decreased with increased pressure, with a maximum value of approximately 8 MPa. When the temperature increased by 10°C, the adsorption capacity decreased by 8.3%, on average. In the subcritical CO2 state, the trend of excess CO2 adsorption in coal was consistent with that of absolute adsorption, which was 16% higher than that of excess adsorption, on average. After the action of supercritical CO2, the propagation velocity of the longitudinal wave in the sample decreased significantly, indicating that supercritical CO2 can effectively promote the development of pores and fractures in the coal sample, with an obvious anti-reflection effect on the coal seam and the best permeability enhancement effect at 35°C.